(untitled) (Research, Society and Development, 2021)
The population presents knowledge about medicinal herbs, due to the habit of cultivating plants in the residential areas and the transmission of ethnobotanical knowledge among individuals in the community, with the purpose of treating diseases. Hyptis pectinata has aromatic characteristics, and can be cultivated in the backyard, although it grows naturally around forests. This study refers to a systemic literature review about the antimicrobial potential from the extracts of the plant Sambacaité (Hyptis pectinata), with search of materials in the SCIELO and PUBMED databases, using the recommendations of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Research selection was carried out in three stages (reading the title and abstract, reading the publications in full, and using the selected articles to form and compile the data). The results obtained in this study, presents effective results of H. Pectinata plant extract for anti-inflammatory, antioxidant, antinociceptive and antiedematogenic antimicrobial effects.